Nocturnal Ovipositioning of Flies - Pritam, Helmi Mohd Hadi (Universiti Sains Malaysia, 2006)
Post-mortem interval (PMI) is calculated by ascertaining the age of the immature stages of blow flies demonstrating the longest period of association with decomposed human remains. The time at which the flies oviposit is generally assumed to be during the day time in which the flies are known to be active. A few researchers have indicated that limited number of flies do oviposit during night hours and under artificial lighting although studies on twilight ovipositioning have not been carried out so far. Moreover, previous researchers have indicated the use of mutton purchased from the market which does not preclude the possibility of flies depositing the eggs in the market place. This thesis is the compendium of findings of a research that addressed, for the first time, the possibility of ovipositioning during twilight as well as using beef purchased directly from the slaughter house in Kota Bharu, Kelantan. The control and night experiments were carried out inside the campus of Universiti Sains Malaysia, Kelantan. The results indicate the possibility of limited ovipositioning during the twilight period which further declines during the night period although ovipositioning is found significantly delayed by 4 to 5 days after continuous exposure of the animal model during the twilight and night time while diurnal oviposition in the control animal model does not indicate such delay. It is argued here that the delayed appearance of limited maggots attributable to nocturnal ovipositioning need not be construed as a factor attributing to estimating longer PMI since the maggots on account of immediate diurnal ovipositioning are the ones that are longer and considered for estimating PMI. It is suggested that PMI has to be estimated only by considering diurnal ovipositioning and the possibility of disposal during night has to be left for the investigating agency to establish through evidence other than entomological.